Les savoirs des prisons : rationalité punitive et savoirs critiques - Gilles Chantraine (Tracés, 2009)
Whether aiming at undermining the myths of the prison system, identifying the dominant rationale for the modern criminal justice system, or objectifying the structural violence of security in prisons, critical knowledge on prisons and criminal justice is motivated by the same belief : that in order to change viewpoints on prisons, researchers should depart from a number of ideas which have been “taken for granted”. These ideas, whether they partake of legal, criminological, sociological or penitentiary knowledge, condemn prisons to endless repetition. Opening up the different fields of knowledge to create new possibilities could well be a definition of the “usefulness” of any research on prisons.